A Reflection on Material Citizenship - Baglioni, Lorenzo Grifone (SocietàMutamentoPolitica, 2016)
The concept of citizenship is central to European history and has great resonance. It does however bear the weight an ‘original sin’, its derivation from the idea of the nation: a relationship worth reviewing in the light of the dynamics of present-day society. Furthermore, the polysemic nature of citizenship can di use its meaning and reduce e ective analysis. With this in mind, the present paper, after having explored the origins of citizenship and reviewed its development, proposes a de nition in material terms. The question of status, pre-eminent in the juridical approach, is of lesser importance in the present sociological interpretation of citizenship, concentrating as it does on individual practices. Rights allow the individual access to certain social resources (which ones?) but capitals determines the quantity of social resources the person may draw on (how many?). Together, rights and capitals shape the capabilities that each person converts into functionings in daily life – that is into the practices of citizenship, but only in those cases when the individual’s behaviour is compatible with the norms of the community.